1987
DOI: 10.1016/0044-8486(87)90069-x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of photoperiodicity, water temperature and an inherent endogenous rhythm for the production of viable eggs by the African catfish, Clarias gariepinus, kept in subtropical ponds in Israel and under Israeli and Dutch hatchery conditions

Abstract: ., 1987. The significance of photoperiodicity, water temperature and an inherent endogenous rhythm for the production of viable eggs by the African catfish, Clark gariepinus, kept in subtropical ponds in Israel and under Israeli and Dutch hatchery conditions. Aquaculture, 63: 169-185.A comparison was made between the fecundity of female African catfish, Clarias gariepinus, transferred from their natural habitat in Northern Israel to nearby fish ponds and an indoor hatchery respectively, and conspecifics reared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

1987
1987
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
0
26
0
4
Order By: Relevance
“…African catfish reared under a constant water temperature of 25°C reach sexual maturity at the age of 6-9 months. They show a continuous ovarian cycle and can be induced to produce large quantities of viable eggs all year round (Richter et al, 1987). Contrary to common carp and African catfish, in perciform species gametogenesis would be impaired at constant high rearing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…African catfish reared under a constant water temperature of 25°C reach sexual maturity at the age of 6-9 months. They show a continuous ovarian cycle and can be induced to produce large quantities of viable eggs all year round (Richter et al, 1987). Contrary to common carp and African catfish, in perciform species gametogenesis would be impaired at constant high rearing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Two consecutive major events take place in the completion of the ovarian cycle. The first one, which concerns the gradual enlargement of ovaries with concomitant formation of yolk‐rich‐oocytes (ovarian recrudescence) in the prespawning period, is dependent on increasing temperature (Richter, Viveen, Eding, Sukkel, Rothuis, Van Hoof, Van Den Bergh & Van Oordt 1987). The second event, which includes maturation, ovulation and oviposition is trigerred by a combination of environmental factors such as a rise in water level and changes in the chemical composition of the water (Bruton 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The second event, which includes maturation, ovulation and oviposition is trigerred by a combination of environmental factors such as a rise in water level and changes in the chemical composition of the water (Bruton 1979). It was shown that the circannual endogenous rhythms in gametogenesis were no longer present in C. gariepinus raised from egg to maturity under constant high temperature (25°C) and adequate food (Richter et al . 1987).…”
Section: Introductionmentioning
confidence: 99%
“…This means that under natural conditions artificial propagation of African catfish can only be applied successfully during the breeding period and the beginning of the resting period. Bringing mature African catfish from their natural habitat to an indoor hatchery under conditions of optimal food supply, constant water temperature of about 25°C and normal local changes in daylength, makes the period of successful artificial propagation increase to 10 or 11 months per year (Richter et al, 1987b). Fish reared from egg to maturity in laboratory tanks under similar feeding and temperature conditions and different photoperiodic regimes showed an uninterrupted ovarian activity with postvitellogenic oocytes at all seasons.…”
Section: Identificationmentioning
confidence: 99%
“…Throughout the year their pituitaries contain large and densely granulated gonadotropes (Peute et al, 1984)) storing large amounts of gonadotropin (De Leeuw et al, 1985a). The gonads of such animals show a continuous cycle with numerous ripe sperm cells and postvitellogenic oocytes at all seasons (Richter and Van Den Hurk, 1982), but without spontaneous spermiation, oocyte maturation and ovulation (Richter et al, 1987b). The absence of a discontinuity in the annual reproductive cycle under favourable husbandry conditions is primarily the result of the absence of a prespawning gonadotropin surge and a postspawning regression of the gonadotropes.…”
Section: Reproductive Cyclementioning
confidence: 99%